ANALISIS STORYTELLING BERBASIS TRANSMEDIA PADA IP KARAKTER HYPNOSIS MIC - Ika Resmika Andelina; Rike Soewandi (Universitas Trisakti, 2021)
Abstract Transmedia Storytelling Analysis on Hypnosis Mic Character IP. Transmedia storytelling is a strategy that is often used in entertainment media to implement an intellectual property (IP). This technique is a way of conveying and telling a narrative across multiple media platforms. The use of the transmedia strategy has a big influence on an IP, one of which is Hypnosis Mic (Hypmic). Hypmic is a collaborative project between hip-hop musicians and seiyuu in the form of a music video with 2D characters. IP Hypmic has many media platforms for storytelling. With the comparative qualitative method, analysis of the story and character samples in the media will be carried out using the hyperdiegesis approach, narrative fabric, and memory. Then make comparisons to find out the differences in them and how the transmedia storytelling technique of each media affects the core story. It is hoped that this research can become a reference material for developing aspects of design strategies and stories on transmedia storytelling that affect the creation of IP, so that content creators can create IPs that have attractiveness in attracting audience.Keywords: transmedia storytelling, intellectual property, character design Abstrak Analisis Storytelling Berbasis Transmedia pada IP Karakter Hypnosis Mic. Transmedia storytelling adalah sebuah strategi yang kerap dipakai dalam media entertainment untuk menjalankan sebuah intellectual property (IP). Teknik ini merupakan cara untuk menyampaikan dan menceritakan sebuah narasi melalui banyak platform media. Penggunaan strategi transmedia memiliki pengaruh besar pada sebuah IP, salah satunya adalah Hypnosis Mic (Hypmic). Hypmic adalah sebuah projek kolaborasi antara pemusik hip-hop dengan seiyuu dalam bentuk video musik dengan karakter 2D. IP Hypmic memiliki banyak platform media untuk bercerita. Dengan metode kualitatif komparasi, akan dilakukan analisis cerita dan sampel karakter pada media-medianya menggunakan pendekatan hyperdiegesis, jalinan naratif, dan memori. Lalu melakukan perbandingan untuk mengetahui perbedaan yang terdapat di dalamnya dan bagaimana teknik transmedia storytelling tiap media berpengaruh pada inti cerita. Hasil penelitian ini dapat menjadi bahan acuan untuk mengembangkan aspek-aspek strategi desain dan cerita pada transmedia storytelling yang memengaruhi penciptaan IP, agar content creator dapat menciptakan IP yang memiliki daya tarik dalam memikat penonton.Kata kunci: transmedia storytelling, intellectual property, desain karakter